A new species of wolf snake (Colubridae: Lycodon Fitzinger, 1826) from Phnom Samkos Wildlife Sanctuary, Cardamom Mountains, southwest Cambodia - Neang, Thy; Hartmann, Timo; Hun, Seiha; Souter, Nicholas J.; Furey, Neil M. (Zootaxa, 2014)
A new species of the genus Lycodon Fitzinger, 1826 is described from the Cardamom Mountains of southwest Cambodia. Lycodon zoosvictoriae distinctly differs from all other species of Lycodon in Southeast Asia by a combination of its morphometric characters and unique coloration. The new species has 17 dorsal scales at midbody; 2+2 temporals; 8 supralabials; 10 infralabials; loreal separated from internasal and orbit; 213 ventrals; 85 subcaudals; pale tan brown ground color; irregular dark brown blotches on anterior part, 31 transverse blotches on posterior part of body and 26 blotches on tail. Given its submontane type locality, the new species could prove to be endemic to the Cardamom Mountains of southwest Cambodia and probably Southeast Thailand.